Effect of Low-Temperature Storage of Placenta on Antioxidant Effect of Its Extracts as for Erythrocytes under Oxidative Stress State Caused by Sodium Nitrite - Narozhnyy, Stanislav V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 178